Petrophysical Characterization and Gas Accumulation of Wufeng-Longmaxi Shale Reservoir in Eastern Margin of Sichuan Basin, SW China - Wei Wang; Dahua Li; Lijun Cheng; Ye Zhang; Jinxi Wang; Zhiping Zhang; Hualian Zhang; Dongxin Guo; Yuelei Zhang; Qing Hua; Jun Liu (Geofluids, 2022)
Shale gas plays a significant role in meeting the increasing demand of energy resources, which enables the exploration and exploitation of gas from shale reservoir to be emphasized gradually. Aiming to serve a more responsible and efficient shale gas development, for example, to guide the hydraulic/nonaqueous fracturing operation, this work organized a comprehensive assessment on the petrophysical characterization and gas accumulation of the Upper Ordovician Wufeng-Lower Silurian Longmaxi shale reservoir (abbreviated as WL shale). Results indicate that the WL shale in Well-YC4 contains three third-order sequences (SS1-lower WL, SS2-middle WL, and SS3-upper WL), and each sequence contains a transgressive system tract (TST) and a high-stand system tract (HST), according to the logging information. Meanwhile, the SS1, SS2, and SS3 experienced variable sedimentary environment—with different relatively oxygenic and hydrodynamics. And the bottom section (SS1 and SS2) has a soft great brittle index (BI) value than the upper section (SS3), suggesting the bottom WL shale is better suited for hydraulic fracturing than the upper section. Besides, the organic matter indicates the WL shale has a decent hydrocarbon generation ability, and the thermal evolution degree is also conducive to the full generation of shale gas. The gas content of WL shale ranges in the scope of 0.76 m3/t~2.38 m3/t, in which CH4 is the primary composition and occupies 95.51%~99.36%, and the content of heavy hydrocarbon gases is limited. Besides, the drying coefficient indicates the dry gas is the dominate molecular composition in the gas content of WL shale. Hopefully, this work is instructive to a certain extent for the researchers and engineers who are working on WL shale gas in Sichuan basin.